Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174100
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Last-mile Logistics

Abstract: Road congestion, air pollution and sustainability are increasingly important in major cities. We look to understand how last-mile deliveries in the parcel sector are impacting our roads. Using formative field work and quantitative analysis of consignment manifests and location data, we identify how the effectiveness of lifestyle couriers is contributing to both environmental and non-environmental externalities. This paper presents an analysis of delivery performances and practices in last-mile logistics in cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…[14] The theme of the abstracts presented here is "The future of techno-disruption in gig economy workforces. " This theme builds on previous work highlighting how HCI and design can (and should) work for workers, not just consumers, to help fight issues of unjust labour practice and shift the power of the gig economy to the hands of workers [2,8]. The abstracts are positioned in the near-future (2025-2035) (cf.…”
Section: Methods Overviewmentioning
confidence: 84%
See 1 more Smart Citation
“…[14] The theme of the abstracts presented here is "The future of techno-disruption in gig economy workforces. " This theme builds on previous work highlighting how HCI and design can (and should) work for workers, not just consumers, to help fight issues of unjust labour practice and shift the power of the gig economy to the hands of workers [2,8]. The abstracts are positioned in the near-future (2025-2035) (cf.…”
Section: Methods Overviewmentioning
confidence: 84%
“…HCI and related studies of digital technology have focused on: protecting gig workers [18]; algorithmic bias and data in the futures of work [13,22]; developing tools to support workers in gig and crowd work [2,8]; configurations of piecemeal work [1]; and, studies of on-demand, gig economy work [7,20]. Whilst gig work is facilitated by technology, the authors also recognise the potential of digital technology to disrupt the labour of work in the UK where the gig economy facilitates casual work for 2.8 million workers [9].…”
mentioning
confidence: 99%
“…A DSP would be able to determine how much each different device type is used from their user analytics data. 4 To estimate this in our study, we use data from two sources. We use publicly available data from YouTube regarding the breakdown between fixed and mobile devices.…”
Section: Methodsmentioning
confidence: 99%
“…Sustainability through Design uses HCI approaches to address broader sustainability challenges. Examples include eco-feedback techniques [16] and social networks [13,32] to reduce an individual's resource use; using mobile support for transport [15]; the use of crowdsourcing to support pro-environmental community activism [34]; using thermal imaging to encourage improved building efficiency [36]; energy-efficient retrofitting [35]; and support for last-mile logistics [4].…”
Section: Related Work Sustainable Interaction Design and Sustainable Hcimentioning
confidence: 99%
“…For example, Allen et al reported that vehicle delays have increased by 31% in central London [20]. Further, Bates et al forecasted that congestion would increase in central London by 60% in 2030 [41]. These issues collectively make it difficult for freight carriers to comply with the time-sensitive delivery requirements of business receivers.…”
Section: Operational Challenges and Issues Of Last Mile Delivery In Tmentioning
confidence: 99%